Improving Learning Outcomes Using Jigsaw Learning in High Class Elementary Schools (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research addresses the challenge of low student learning outcomes and limited group learning engagement. Specifically, it seeks to enhance students' thematic learning outcomes by implementing the Jigsaw learning model. Methodology: The study employs a classroom action research design conducted over three cycles. The subjects of this research were 34 students from class VI.B at Elementary School 25 Palembang. Data collection techniques included observation, tests, and documentation to gather comprehensive student performance and engagement insights. Main Findings: The research findings indicate a significant improvement in student learning outcomes due to applying the Jigsaw learning model. The thematic learning outcomes for theme 1, subtheme 2, showed a marked increase across the three cycles: from 53% in cycle I to 65% in cycle II and 88% in cycle III. This progression highlights the model's effectiveness in fostering better academic performance and active participation among students. Novelty/Originality of this study: The novelty of this research lies in its application of the Jigsaw learning model within the context of thematic learning, which is relatively underexplored in primary education. The study enhances cognitive outcomes and promotes social skills and collaborative learning by integrating cooperative learning strategies that emphasize student interdependence and accountability. This innovative approach demonstrates the potential of the Jigsaw model to transform traditional classroom dynamics, making learning more interactive, inclusive, and effective. Thus, the study provides valuable insights and practical implications for educators seeking to improve student engagement and achievement through collaborative learning models.